(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
According to recent studies, dry hard turning is more beneficial practical process compared to a grinding operation, it increases quality, reduces cost and lead-time for machined parts. In this study, effects of workpiece hardness, feed rate, depth of cut and cutting speed on surface roughness were studied using chamfered and honed CBN inserts. Four factors (hardness, depth of cut, feed rate and cutting speed) were considered and - two level fractional experiments were conducted and analysis of the variance was performed. Furthermore this study shows that the effects of grinding of heat treated AISI D2 specimens on surface roughness were conducted and a comparison took place with hard turning. To investigate the effect temperature increase on both techniques, the machined surface of workpieces is examined using optical and scanning electron microscopy SEM. Practical results shows the lower workpiece hardness and lower cutting conditions resulted in a better surface roughness. Finally results showed that in hard machining not only the machining parameters have an influence on the surface roughness but also the material hardness found effective factor in finishing process.